Omnidirectional walking of a four legged robot - Magpantay, Percival C. (2006)
"The use of legged vehicles or robots, in place of the usual wheeled vehicles, overcomes the difficulties of traversing an irregular terrain but with a decrease in speed and increase in control complexity. This study implemented a walking algorithm based on a hierarchical behavior-based control architecture, with behaviors confined to leg controllers linked by a serial network. The algorithm generated a crawl gait and was tested on a four legged robot platform developed in the Mobile Robotics Laboratory, UP Diliman. The robot was able to walk forward, backward and sideways on a flat surface under certain initial leg configurations."